DINAMIKA MUSIMAN KUALITAS AIR DI DAERAH SUNGAI KAHAYAN KALIMANTAN TENGAH - Elyta Vivi Yanti (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
This study is aimed to investigate effect of nutrient contained chlorophyll-a and the influence of physical, chemical water quality of the chlorophyll-a. Because the dynamics of nutrients that affect primary productivity, which can cause changes in the conditions these waters.Research was conducted at the Kahayan River and back water is called Lake Tehang, connecting channel between Lake Tehang and Lake Batu, Lake Tehang nearby port, Lake Tehang at the middle part, Lake Bunter, Kahayan River of Kota Palangka Raya from Oktober 2015-Desember 2015 rainy seasonal and Juli 2015-September 2015 dry seasonal by measuring monthly some water quality parameters such as water level or depth (WL), water temperature (WT), Total Suspendid Solid (TSS), electrical conductivity (EC), pH, dissolved oxygen (DO), nitrat (NO3), nitrit (NO2), fosfat (PO4), total nitrogen (TN), silikat (SIO2), ammonia (NH3), total fosfat (TP), chlorophyll-a. Those water quality parameters were regarded as independent countinous variables which were measured insitu by using depth sounder for WL and Horiba U10 water quality checker for WT, EC, pH and DO. However, for TSS, NO3, NO2, TP, PO4, TN, SIO2, NH3 and chlorophyll-a were analyzed in the laboratory. To extract these multivariable data, I used Redudancy Analysis (RDA) of statistical program of R. Result showed that there were clearly relationship among water quality parameters, factor of chemical physics at study site by biplot ordination graph (map) of RDA. and water temperature was simultaneously affected significantly by water quality parameters, WL, source (F= 0.09, Pr(>F) = 0.005). The RDA exhibited the brief tendency that strongly possitive correlation occurred among WL, EC, in turn the negatif correlation with WT, pH and DO by both RDA1 and RDA2 axis. In addition WT were also strongly possitive correlation happened among them, and on the other hand negatif correlation to WL RDA1 and RDA2 axis. By constraining all independent variables, I found that WT were among the significant variables affecting mortality of fish and respectively showing by anova permutation test : WT: F = 0,03, Pr(>F) = 0.005; F : 0,09, Pr (>F)= 0,19.Chemical physics factors are chlorophyll-a gave an impulse to the development of chlorophyll-a in the water, chlorophyll-a in waters influenced by the total phosphate, and silikat (SIO2. In river and lakes of high latitude the large annual fluctuation of water temperature affects aquatic communities including phytoplakton